(untitled) (CIPEEX, 2022)
LEGAL DESIGN IS A TOOL THAT SEEKS TO MAKE LAW MORE SIMPLIFIED, ATTRACTIVE, AND UNDERSTANDABLE TO LAY PEOPLE; IT IS THE HUMANIZATION OF LAW. ALTHOUGH THE USE OF DESIGN AS A STRATEGY IN LAW HAS GAINED MORE SPACE RECENTLY, THE TOOL HAS BEEN THE SUBJECT OF STUDIES AND RESEARCH FOR OVER A DECADE IN MAJOR UNIVERSITIES AROUND THE WORLD. WE LIVE IN A SOCIETY THAT COMMUNICATES MORE AND MORE THROUGH IMAGES, A GENERATION THAT IS INCREASINGLY CONNECTED TO SCREENS, AND THIS IS CHANGING THE WAY WE COMMUNICATE AND HOW WE CHOOSE TO RECEIVE INFORMATION. CONSEQUENTLY, THIS IS IMPACTING THE LAW, WHICH USED TO HAVE TEXTUAL RESOURCES AS ITS MAIN LANGUAGE, AND NOW SEES THE NEED FOR TRANSFORMATION TO KEEP UP WITH THE DEVELOPMENT OF A WORLD THAT INCREASINGLY VALUES FAST, EFFECTIVE, SHAREABLE, AND SIMPLE COMMUNICATION. AMONG THE MAIN LEGAL DOCUMENTS, CONTRACTS ARE THE ONES THAT MOST REFLECT THE NEED FOR IMPROVEMENTS IN THE COMMUNICATION WITH USERS, BECAUSE THEY ARE THE ONES THAT TRANSLATE THE WILLS OF THE PARTIES AND THE CONSENSUS THEY WISH TO CREATE, BEING AN IMPORTANT INSTRUMENT OF COLLABORATION AND COMMUNICATION. IT HAPPENS THAT USERS, ESPECIALLY THE LAYMEN, HAVE A LOT OF DIFFICULTY IN UNDERSTANDING THE DOCUMENT, DUE TO THE SOPHISTICATED LANGUAGE, LONG AND VISUALLY UNINTERESTING TEXTS THAT MAKE THE READING TIRESOME. ALL THESE ELEMENTS MAKE CONTRACTS SEEM TO BE DOCUMENTS PREPARED BY LAWYERS FOR LAWYERS TO UNDERSTAND, EVEN IF THE MAIN CHARACTERS ARE THE NEGOTIATION PARTIES THEMSELVES. HOW CAN WE EXPECT THE PARTIES TO ABIDE BY THE CONTRACT IF THEY CANNOT THEMSELVES CONSULT OR UNDERSTAND THE CONTENT OF THE INSTRUMENT? THUS, CONTRACTS THAT SHOULD HAVE COMMUNICATION AS THEIR ROLE, END UP ISOLATING THE PARTIES, AFFECTING THEIR EFFECTIVENESS AND EFFICIENCY, A DOCUMENT THAT SHOULD BE SYNONYMOUS WITH AGREEMENT BECOMES ONE MORE LITIGATION TAKEN TO COURT. ACCORDING TO MARGARET HAGAN (2022) LEGAL DESIGN IS A METHODOLOGY THAT FOCUSES ON THE USER EXPERIENCE TO CREATE NEW WAYS TO TRANSLATE COMMUNICATION, ADAPTING LANGUAGE SO THAT DOCUMENTS, ESPECIALLY CONTRACTS, CAN BE UNDERSTOOD. THE PRESENT STUDY STARTED THROUGH BIBLIOGRAPHIC RESEARCH THAT ALLOWED A BROADER VIEW OF THE SUBJECT IN QUESTION, AND WAS FINALLY CONSOLIDATED WITH THE ACTUAL ANALYSIS OF THE EXPERIENCE OF CONTRACT USERS THROUGH ONLINE INTERVIEWS USING GOOGLE FORMS, A FIELD RESEARCH THAT IS IN PROGRESS. TO DATE, IT IS NOTICEABLE THAT TRADITIONAL CONTRACTS DO NOT ALWAYS ACHIEVE A REAL UNDERSTANDING OF THEIR TERMS AND CONDITIONS BY THE PARTIES THAT ENTER INTO THEM, ESPECIALLY IF THESE PARTIES LACK ADEQUATE EDUCATION. THUS, TO MOVE AWAY FROM THE CONVENTIONAL WAYS IN WHICH CONTRACTS ARE DRAWN UP AND IN FACT ACHIEVE GREATER EFFECTIVENESS IN COMMUNICATION AND NEGOTIATING AUTONOMY OF THE PARTIES, LEGAL DESIGN BECOMES AN INNOVATIVE TOOL THAT ENCOURAGES USERS TO SEEK THEIR RIGHTS AND IDENTIFY THEM IN EVERYDAY LIFE, DIRECTING LAWYERS TO CREATE MORE INTELLIGENT DOCUMENTS THAT CAN HELP PEOPLE MAKE WISE DECISIONS, OPTIMIZING THE USER EXPERIENCE.